(untitled) (Bioagro, 2018)
This study determined the suitable zones for planning apple growing in Mala’s valley, Peru, using analytical hierarchy process (AHP) in a geographic information system (GIS) environment. The suitability evaluation involved the analysis of nine criteria organized into four groups (soil, topography, hydro-climate and socioeconomic). Based on key informants assessments relative weights were assigned to each nine criteria using the AHP. A digital GIS database was developed with all the thematic maps. The criteria were reclassified before combination, according to a four-class system for suitability. Then, a summarized process was done by applying the weights to each criterion, followed by a summation of the results to yield a suitability map using GIS. Layer and weight sensitivity methods combined with Kappa analysis were carried out in order to prove the robustness of the suitability model. The results revealed that about 12.57 % (9953 ha) of agricultural area are suitable for apple cultivation and out of which 3.98 % and 3.37 % are highly and moderately suitable, respectively. If farmers in the valley considered growing apple crops in the 3149 ha (highly suitable), the gross profit would have substantial increase. Therefore, the final map can become a useful tool of territorial governance and policy in order to assist in the agricultural expansion process of Mala’s valley.